Effective Practices for Helping Students Transition to Work - Aston, Desmond; Mc Guckin, Conor; Shevlin, Michael; Kubiak, John; Ringwood, Barbara (Oxford University Press, 2020)
People with disabilities have been among the most marginalized groups within society, with consequent limitations imposed on their access to many goods within society, including education, employment, and economic independence. Some progress is evident in the establishment of more inclusive learning environments, yet it is also clear that upon leaving compulsory education or further/higher education, young people with disabilities encounter significant barriers to accessing meaningful employment. Facilitating transitions to employment for people with disabilities should be informed by ambition and a belief in the capacity of these individuals to make a meaningful contribution to society and achieve a level of economic independence. The issues that are pertinent to young people who have a special educational need or a disability and an aspiration to transition to further/higher education require attention. Research and applied practice has demonstrated the utility of an innovative educational and work readiness program for people with an intellectual disability. Such work highlights the facilitating factors that may encourage a more ambitious reimagining of what may be possible for individuals who have been marginalized.
Oxford Research Encyclopedia of Education
PUBLISHED
Keywords: Employment; Disability; Intellectual disability; Ireland; Special educational needs; Transitions; Inclusive Society; EDUCATION; Education and Work; INTELLECTUAL DISABILITY; TRANSITION; Transitioning to work for students with disabilities; Intellectual Disability; Education; Employment; Social participation